Preparation method and application of toona sinensis extract corrosion inhibitor

By using the toon extract as a corrosion agent, the problem of self-corrosion of aluminum-air batteries in an alkaline environment is solved, the performance and life of the battery are improved, and the defects of traditional corrosion doses are reduced.

CN119372654AInactive Publication Date: 2025-01-28INNER MONGOLIA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411961468.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aluminum-air batteries have self-corrosion problems in alkaline environments, resulting in limited battery performance and life. Traditional corrosion inhibitors have problems such as high toxicity, pollution of the environment, high cost and complex synthesis.

Method used

Use toon extracts as a corrosion agent. By preparing the toon extract by steps such as the toon leaves or buds in the past, and the electrolytes of the aluminum -air battery were added to the electrolytes of aluminum air batteries to suppress aluminum to suppress aluminum battery battery Aodic corrosion.

Benefits of technology

Effectively suppress the self -corrosion of aluminum anode, improve the stability and discharge performance of the electrolyte, significantly enhance the anode utilization rate, and reduce the rate of hydrogen analysis, and improve the corrosion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372654A_ABST
    Figure CN119372654A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a toona sinensis extract corrosion inhibitor, and the preparation method of the toona sinensis extract corrosion inhibitor comprises the following steps: cleaning toona sinensis with deionized water, drying, and grinding into toona sinensis powder by a grinder; adding the cedrela sinensis powder into deionized water, boiling for 2-4 hours, and removing filter residues through vacuum filtration to obtain a mixed solution containing a cedrela sinensis extract and water; and performing vacuum freeze drying on a mixed solution containing the cedrela sinensis extract and water, and grinding the mixed solution into powder by using a mortar to obtain the cedrela sinensis extract. The problems of high toxicity, environmental pollution, high cost, complex synthesis and the like of the existing corrosion inhibitor are solved, and the problem of low battery capacity caused by serious anode corrosion of the zinc-air battery under the existing condition technology is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-air batteries, and in particular to a preparation method and application of a toon extract corrosion inhibitor. Background Art

[0002] With the growth of fossil fuel consumption and environmental concerns, clean and sustainable development technologies such as electrochemical devices and membrane bioreactors are very popular in the future renewable energy market. Aluminum-air batteries are a type of metal-air batteries with high energy density and environmental friendliness. They have attracted widespread attention due to their potential high theoretical energy density, high theoretical capacity and simple electrochemical principles. Aluminum-air batteries use metal aluminum as the anode and oxygen in the air as the cathode reactant to generate electricity through electrochemical reactions. Especially under alkaline electrolyte conditions, the redox reaction of aluminum exhibits excellent electrochemical properties, making alkaline aluminum-air batteries show great application prospects in energy storage devices, portable power sources and other fields. However, the self-corrosion problem of aluminum anode in alkaline environment seriously restricts the performance and life of the battery.

[0003] In alkaline electrolytes, the aluminum surface reacts easily with hydroxide ions to form aluminum oxide or aluminum hydroxide. These oxide and hydroxide layers not only hinder the effective electrochemical reaction, but also easily form a local battery effect, accelerating the corrosion process of aluminum. In order to slow down the self-corrosion of aluminum in an alkaline environment, the method of adding corrosion inhibitors is usually adopted. However, the commonly used traditional inorganic corrosion inhibitors and organic corrosion inhibitors have problems such as high toxicity, environmental pollution, high cost and complex synthesis, which seriously limit their large-scale application.

[0004] In recent years, plant extracts are considered to be an environmentally friendly, safe, readily available, non-toxic, biodegradable and renewable natural green electrolyte corrosion inhibitor. They are rich in compounds such as phenylpropanoids, flavonoids, tannins, amino acids, etc., which can act as active centers to promote the adsorption of molecules on the metal surface and inhibit the corrosion of metals. Therefore, exploring efficient and environmentally friendly natural electrolyte corrosion inhibitors is one of the key research directions at present. Summary of the invention

[0005] Based on this, the present invention provides a preparation method and application of a toon extract corrosion inhibitor, which solves the problems of high toxicity, environmental pollution, high cost and complex synthesis of existing corrosion inhibitors, and severe corrosion of the anode of zinc-air batteries under existing technical conditions, resulting in low battery capacity.

[0006] In order to solve the above technical problems, one of the objects of the present invention is to provide a method for preparing a toon extract corrosion inhibitor, comprising the following steps: S1: Wash the leaves or buds of Toona sinensis with deionized water, dry them, and grind them into Toona sinensis powder using a grinder; S2: adding the toona sinensis powder to deionized water and boiling for 2-4 hours, removing the residue by vacuum filtration to obtain a mixed solution containing the toona sinensis extract and water; S3: The mixed solution containing the Toona sinensis extract and water is freeze-dried in vacuum, and then ground into powder using a mortar to obtain the Toona sinensis extract.

[0007] Preferably, the particle size of the Toona sinensis powder in S1 is 200 mesh.

[0008] Preferably, the drying temperature in S1 is 40-60° C., and the drying time is 24-48 h.

[0009] Preferably, the mass ratio of the toon powder to the deionized water in S2 is 1:20-30.

[0010] Preferably, the vacuum freeze-drying in S3 is carried out at a temperature of -80°C to -100°C and for a time of 24-48 h.

[0011] Based on the same inventive concept, the present invention also provides an application of a corrosion inhibitor, wherein the corrosion inhibitor is used in a high-efficiency aluminum-air battery electrolyte, and the electrolyte is composed of 0.02-0.05 parts of corrosion inhibitor, 16 parts of strong alkali, and 95-105 parts of deionized water.

[0012] Preferably, the strong base is one or both of sodium hydroxide and potassium hydroxide.

[0013] The mechanism of action is: in the aluminum-air battery reaction, the corrosion inhibitor extracted from toon contains a variety of bioactive compounds, such as toon phenol, toon phenol, polyphenol compounds, flavonoids, etc. These substances are preferentially adsorbed on the surface of the aluminum anode and produce a protective film to prevent water molecules from directly contacting the surface of the aluminum anode, inhibiting the electrochemical corrosion reaction of the metal, and significantly enhancing the discharge performance and anode utilization.

[0014] The above one or more technical solutions of the present invention have the following technical effects: (1) The present invention uses the Toona sinensis extract as a corrosion inhibitor, which broadens the electrochemical stability window of the electrolyte and improves the stability of the electrolyte; (2) In the present invention, as the concentration of the toon extract corrosion inhibitor increases, the corrosion rate gradually decreases; (3) When the electrolyte prepared by the present invention is used on the surface of aluminum anode, it can effectively inhibit self-corrosion, reduce the hydrogen evolution rate, and improve the corrosion inhibition efficiency; (5) When the electrolyte prepared by the present invention is used in an aluminum-air battery, it can effectively improve the discharge performance of the aluminum-air battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0016] Figure 1 , Preparation process of corrosion inhibitor for aluminum-air battery; Figure 2 , polarization curves of Examples 4-7 and Comparative Examples; Figure 3 , Nyquist plots of Examples 4-7 and Comparative Examples; Figure 4 , electrochemical Bode fitting spectra of Examples 4-7 and Comparative Examples; Figure 5 , electrochemical phase angle fitting spectra of Examples 4-7 and Comparative Examples; Figure 6 , open circuit potential curves of three-electrode systems assembled from Examples 4-7 and Comparative Examples; Figure 7 , hydrogen evolution volume diagram of Examples 4-7 and Comparative Example; Figure 8 , hydrogen evolution rate and hydrogen evolution inhibition efficiency diagram of Examples 4-7 and Comparative Examples; Fig. 9 , in-situ optical microscope images of Example 6 and the comparative example; Fig.10 , constant current discharge curves of the aluminum-air batteries assembled from Example 6 and the comparative example; Fig.11 , the cycle discharge curves of the aluminum-air batteries assembled from Example 6 and the comparative example; Fig.12 , voltage curves of the aluminum-air batteries assembled in Example 6 and the comparative example at different current densities; Fig.13 , polarization curves of the aluminum-air batteries assembled from Example 6 and the comparative example; Fig.14 , power density curves of the aluminum-air batteries assembled from Example 6 and the comparative example. DETAILED DESCRIPTION

[0017] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0018] Throughout the specification, unless otherwise specified, the terms used herein should be understood as the meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. If there is a conflict, the present specification takes precedence. Figure 1 shown.

[0019] Example 1 A method for preparing a toon extract corrosion inhibitor comprises the following steps: S1: Wash the leaves or buds of Toona sinensis with deionized water, dry them at 40°C for 48 h, and grind them into Toona sinensis powder with a particle size of 200 mesh using a grinder; S2: 80 g of toona sinensis powder was added to 1.6 L of deionized water and boiled for 2-4 hours, and the residue was removed by vacuum filtration to obtain a mixture containing toona sinensis extract and water; S3: freeze-drying the mixture containing the Toona sinensis extract and water at -80°C in vacuum for 48 hours, and then grinding it into powder using a mortar to obtain the Toona sinensis extract.

[0020] Example 2 A method for preparing a toon extract corrosion inhibitor comprises the following steps: S1: Wash the leaves or buds of Toona sinensis with deionized water, dry them at 60°C for 24 h, and grind them into Toona sinensis powder with a particle size of 200 mesh using a grinder; S2: 80 g of toona sinensis powder was added to 2.4 L of deionized water and boiled for 2-4 hours, and the residue was removed by vacuum filtration to obtain a mixture containing toona sinensis extract and water; S3: freeze-drying the mixture containing the Toona sinensis extract and water at -100°C for 24 h in vacuum, and then grinding it into powder using a mortar to obtain the Toona sinensis extract.

[0021] Example 3 A method for preparing a toon extract corrosion inhibitor comprises the following steps: S1: Wash the leaves or buds of Toona sinensis with deionized water, dry them at 50°C for 24 h, and grind them into Toona sinensis powder with a particle size of 200 mesh using a grinder; S2: 80 g of toona sinensis powder was added to 2 L of deionized water and boiled for 2 hours, and the residue was removed by vacuum filtration to obtain a mixture containing toona sinensis extract and water; S3: The mixture containing the Toona sinensis extract and water was freeze-dried at -80°C in vacuum for 48 hours, and then ground into powder using a mortar to obtain the Toona sinensis extract.

[0022] Example 4 Weigh 16 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.02 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 mL volumetric flask to obtain a corrosion inhibitor concentration of 200 mg·L -1 High-efficiency aluminum-air battery electrolyte.

[0023] Example 5 Weigh 16 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.03 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 mL volumetric flask to obtain a corrosion inhibitor concentration of 300 mg·L -1 High-efficiency aluminum-air battery electrolyte.

[0024] Example 6 Weigh 16 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.04 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 mL volumetric flask to obtain a corrosion inhibitor concentration of 400 mg·L -1 High-efficiency aluminum-air battery electrolyte.

[0025] Example 7 Weigh 16 g of NaOH and dissolve it in deionized water. After cooling to room temperature, add 0.05 g of the corrosion inhibitor prepared in Example 3 and adjust the volume to a 100 mL volumetric flask to obtain a corrosion inhibitor concentration of 500 mg·L -1 High-efficiency aluminum-air battery electrolyte.

[0026] Comparative Example Weigh 16 g of NaOH and dissolve it in deionized water. After cooling to room temperature, dilute it to a 100 mL volumetric flask to obtain 100 mL of 4 mol / L sodium hydroxide solution.

[0027] In order to further verify the effect of the electrolyte prepared by the present invention on the self-corrosion performance and discharge performance of the aluminum anode, test examples 1-4 were respectively subjected to electrochemical tests, hydrogen evolution tests, discharge performance tests, and corrosion degree tests of metal aluminum electrodes. Among them, industrial pure aluminum with a purity of 99.99% was used as the aluminum negative electrode of the alkaline aluminum-air battery. Before the experiment, it was polished with 400, 800, 1500, and 2000 grit sandpaper in turn, and then ultrasonically washed with anhydrous ethanol and deionized water in turn, and then dried at room temperature. The specific test examples are as follows:

[0028] Test Example 1 Electrochemical tests were performed on the electrolytes prepared in Examples 4-7 and Comparative Examples to measure polarization curves (Tafel), electrochemical impedance spectroscopy (EIS) and open circuit potential (OCP). The specific test results are shown in Tables 1-2 and Figure 2-5 shown.

[0029] (1) The measurement results of the polarization curve (Tafel) are shown in Table 1 and Figure 2 As shown: Table 1 Tafel curve data results of aluminum electrodes in Examples 4-7 and Comparative Examples

[0030] from Figure 2 It can be seen that the anodic branch of the polarization curve moves to the low current density region, indicating that the corrosion inhibitor acts as an anodic corrosion inhibitor and inhibits the dissolution of the metal anode. As can be seen from Table 1, the addition of corrosion inhibitors will cause the anode Tafel slope (| β a |) increases, which means that when the potential changes to a certain extent, the change in current density is small, which shows that the corrosion inhibitor does have an inhibitory effect on the anodic reaction. In addition, after adding the corrosion inhibitor, the corrosion potential ( E corr ) further confirmed that the corrosion inhibitor is an anodic corrosion inhibitor that achieves its corrosion inhibition effect by inhibiting the anodic reaction. i corr ) from 36.0 mA cm -2 Down to 18.3 mA cm -2 , the maximum corrosion inhibition efficiency reaches 49.2%.

[0031] (2) The measurement results of electrochemical impedance spectroscopy (EIS) are shown in Table 2 and Figure 3-5 As shown: Table 2 Fitting results of impedance spectra of aluminum electrodes in Examples 4-7 and Comparative Example 1

[0032] Figure 3 It can be seen that the radius of the three impedance rings increases with the addition of corrosion inhibitor, and reaches the maximum value in Example 6. This indicates that the corrosion rate is the lowest. The corresponding Bode amplitude and phase angle diagrams are shown in Figure 4-5 As shown, in the presence of corrosion inhibitor, the two time constants at high and low frequencies as well as the phase angle peak show similar trends as those observed in the Nyquist plot, further confirming the reduction in corrosion rate. R T is the polarization resistance. R T The value increases with the addition of corrosion inhibitor. In Example 6, R T The value reaches 2.35 Ω cm 2 The maximum corrosion inhibition efficiency is 51.9%.

[0033] (3) The test results of open circuit potential (OCP) are as follows: Figure 6 As shown: The addition of different concentrations of corrosion inhibitors significantly increased the open circuit potential (OCP), indicating that the adsorption of inhibitor molecules on the aluminum surface hindered the direct contact between aluminum and NaOH solution, thereby suppressing the anodic dissolution of aluminum.

[0034] As shown in Table 1-2 and Figure 2-6 It can be shown that with the increase of the concentration of Toona sinensis extract, the radius of the impedance spectrum increases, the polarization resistance increases, the corrosion current decreases, and its corrosion inhibition efficiency can reach 51.9%.

[0035] Test Example 2 The electrolytes prepared in Examples 4-7 and Comparative Example were subjected to hydrogen evolution tests respectively, and the hydrogen evolution rate was determined by the water displacement method. The aluminum sample was immersed in the electrolyte for 30 minutes, and the amount of liquid discharged was recorded every 5 minutes. Figure 7 As shown in Figure 2, in the presence of Toona sinensis extract, the precipitation volume of H2 is significantly reduced. Figure 8 As shown: with the increase of the concentration of Toona sinensis extract, the hydrogen evolution rate decreased, and the inhibition efficiency of hydrogen evolution could reach 46.7%.

[0036] Test Example 3 The metal aluminum electrode was placed in the electrolyte prepared in Example 6 and the comparative example to perform in-situ surface analysis to observe the surface changes of the metal aluminum. The entire monitoring process lasted for 20 minutes.

[0037] like Fig. 9 As shown, an in-situ optical microscope was used to observe the surface morphology of the aluminum anode. In the comparative example, as time went on, the pitting on the aluminum anode surface gradually increased, and after 20 minutes the entire surface was covered with pitting. In the electrolyte of the comparative example, pitting occurred rapidly on the aluminum anode, indicating that its corrosion rate was high. In the electrolyte of Example 6, the increase in pitting was significantly slowed, indicating that the Toona sinensis extract effectively protected the aluminum anode surface and reduced the corrosion rate.

[0038] Test Example 4 To verify the effect of electrolyte on the discharge performance of aluminum-air battery, the electrolytes prepared in Example 6 and the comparative example were placed in plastic washing bottles, connected to the full battery device, and the battery was connected to a circulation pump to circulate the electrolyte at a rate of 5 mL / min. The measurement was performed at 20 mA cm -2 The constant current discharge curve and cyclic discharge curve under the condition of current density of 20 mA cm -2 The discharge was performed for 1 h under open circuit conditions and 20 min under open circuit conditions for a total of five cycles. -2 The step discharge curve under the condition of linear sweep voltammetry (LSV, 5 mV S -1 ) to generate the polarization curve of the battery.

[0039] Table 3 Average discharge parameters of comparative example and example 6 at constant current discharge for 1 h

[0040] Table 3 and Figure 10-14 As shown in Table 3, the mass change of the aluminum anode is significantly reduced before and after constant current discharge for 1 hour. The capacity density of the metal aluminum in Example 6 reaches 2571.4 mAh g -1 , the energy density reaches 2905.7 Wh kg -1 The anode utilization rate reached 83.9%, which was significantly higher than that of the control group. After adding the toona sinensis extract, the power density increased from 44.06 mW cm -2 Increased to 60.93 mW cm -2 . Fig.10 Using the discharge test, the capacity density of Example 6 is significantly improved. Fig.11 Using the cyclic discharge test, Example 6 is significantly more stable than the comparative example. Fig.12 A multi-step discharge test was performed with the current density gradually increasing to 5, 10, 20, 40, 60 and 80 mA cm -2 When the discharge voltage of the battery containing toon extract drops less than that of the control group, the voltage remains stable during each discharge time. Figure 13-14 Using LSV test, at different current densities, Fig.13 The voltage of Example 6 is higher than that of the comparative example, and the corresponding Fig.14 The power density is also improved.

Claims

1. A method for preparing a toon extract corrosion inhibitor, characterized in that: The steps include: S1: Wash the leaves or buds of Toona sinensis with deionized water, dry them, and grind them into Toona sinensis powder using a grinder; S2: adding the toona sinensis powder to deionized water and boiling for 2-4 hours, removing the residue by vacuum filtration to obtain a mixed solution containing the toona sinensis extract and water; S3: The mixed solution containing the Toona sinensis extract and water is freeze-dried in vacuum, and then ground into powder using a mortar to obtain the Toona sinensis extract.

2. The method for preparing the toon extract corrosion inhibitor according to claim 1, characterized in that: The particle size of the toon powder in S1 is 200 meshes.

3. The method for preparing the toon extract corrosion inhibitor according to claim 1, characterized in that: In S1, the drying temperature is 40-60°C and the drying time is 24-48 hours.

4. The method for preparing the toon extract corrosion inhibitor according to claim 1, characterized in that: The mass ratio of the toon powder to the deionized water in S2 is 1:20-30.

5. The method for preparing the toon extract corrosion inhibitor according to claim 1, characterized in that: The vacuum freeze drying in S3 is carried out at a temperature of -80°C to -100°C and for a time of 24-48 hours.

6. An application of a corrosion inhibitor prepared by the method according to any one of claims 1 to 5, characterized in that: The corrosion inhibitor is used for a high-efficiency aluminum-air battery electrolyte, and the electrolyte consists of 0.02-0.05 parts of the corrosion inhibitor, 16 parts of a strong base, and 95-105 parts of deionized water.

7. The use of the corrosion inhibitor according to claim 6, characterized in that: The strong base is one or both of sodium hydroxide and potassium hydroxide.

Citation Information

Patent Citations

  • Electronic atomized liquid for oral care

    CN113599429A

  • Pharmaceutical application of toona sinensis seed polyphenol

    CN115006447A

  • Simple food for reducing blood fat of pet dog

    CN119054831A